Large-scale recrystallization of the S-layer of Bacillus coagulans E38-66 at the air/water interface and on lipid films. - Pum, D (1993)
S-layer protein isolated from Bacillus coagulans E38-66 could be recrystallized into large-scale coherent monolayers at an air/water interface and on phospholipid films spread on a Langmuir-Blodgett trough. Because of the asymmetry in the physiochemical surface properties of the S-layer protein, the subunits were associated with their more hydrophobic outer face with the air/water interface and oriented with their negatively charged inner face to the zwitterionic head groups of the dipalmitoylphosphatidylcholine and dipalmitoylphosphatidylethanolamine (DPPE) monolayer films. The dynamic crystal growth at both types of interfaces was first initiated at several distant nucleation points. The individual monocrystalline areas grew isotropically in all directions until the front edge of neighboring crystals was met. The recrystallized S-layer protein and the S-layer-DPPE layer could be chemically cross-linked from the subphase with glutaraldehyde.